Cases and materials on land use - Callies, David L. (West Pub. Co., 1986)
The 5th edition covers the entire range of modern land use legal practice and constitutional litigation from the onset of Euclidean zoning through the wide range of new issues arising in the 21st century. Completely new are developments in takings law from Kelo on public purpose and the state backlash, as well as Lingle?s explication of regulatory takings and substantive due process. New cases on accessory uses, zoning out competitors, and contract zoning accompany the classic cases of the prior edition. Topics covered include regulation of formula businesses, sustainability and green standards, new urbanism, transit oriented development, mixed use and the resurgence of large scale new towns, new perspectives on affordable housing, revitalization of cities in light of the mortgage crisis affecting suburban sprawl, new regional and state policies for growth management, conservation of water and monetization of solar energy. There is enhanced coverage of the Clean Water Act (TMDLs) and wetlands (the Rapanos case) and of disaster planning for fire hazards and flooding. This edition is a must to meet the felt needs of students and professors to engage in a new century of creative legal thinking for real world problems and solutions.